1988
DOI: 10.1007/bf02554358
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the anal ducts

Abstract: The records of 21 patients treated for adenocarcinoma of the anal ducts between 1943 and 1982 were reviewed. The patients were followed until death or current status in April 1987. The median follow-up period was eight months (range, 3 to 144 months). Fifteen patients had an erroneous diagnosis made at first physician visit resulting in a median doctor's delay of 14 months (range, 3 to 24 months) before correct treatment was carried out. Nine of the tumors were localized perianally (ischiorectal space), seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
8

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 4 publications
0
47
0
8
Order By: Relevance
“…The reported prognosis has been uniformly poor for this group of patients. 34,36 Surprisingly, our survival and recurrence rates at 5 years were 63% and 21%, respectively. Two factors may be responsible for the high survival rate: the majority of our tumors (78%) were small (Ͻ5 cm), and chemoradiotherapy was used either preoperatively or postoperatively for larger tumors (Ͼ5 cm).…”
Section: Discussionmentioning
confidence: 65%
“…The reported prognosis has been uniformly poor for this group of patients. 34,36 Surprisingly, our survival and recurrence rates at 5 years were 63% and 21%, respectively. Two factors may be responsible for the high survival rate: the majority of our tumors (78%) were small (Ͻ5 cm), and chemoradiotherapy was used either preoperatively or postoperatively for larger tumors (Ͼ5 cm).…”
Section: Discussionmentioning
confidence: 65%
“…Nevertheless, we feel that, based on the histologic and anatomic evidence, this patient's tumor was best classified as an anal gland adenocarcinoma. As was the case with our patients, the majority of patients in previous reports have had extensive disease at the time of presentation, making successful treatment difficult [10]. The standard treatment option for these patients has been surgical.…”
Section: Discussionmentioning
confidence: 77%
“…A review of the literature revealed fewer than 120 cases of this disease (Table 1) [2][3][4][5][6][7][8][9][10][11][12][13][14]. Early diagnoses is difficult, as the symptoms are nonspecific and appear late.…”
Section: Discussionmentioning
confidence: 99%